Model władzy w państwach postsowieckich (Politeja, 2016)
The Model of Power in the Post-Soviet StatesThe aim of this article is to show the evolution of the model of power in the former Soviet states on the example of Belarus, Azerbaijan and Central Asian states (Kazakhstan, Kyrgyzstan, Uzbekistan, Tajikistan and Turkmenistan). The research task of this article is to answer the following questions: Why in the post-Soviet states the most attractive and the most effective is the quasi-authoritarian system? Which factors influenced on deep-rooted authoritarianism in analyzed counties? Why the post-Soviet republics society accepts such a model? And finally, are any chances of the regime’s transition towards the classical democratic system? The role of the referendum in increasing the power of the president will be explored, too.